2021
DOI: 10.1039/d0ra10443d
|View full text |Cite|
|
Sign up to set email alerts
|

In-depth first-principle study on novel MoS2 polymorphs

Abstract: 14 new MoS2 polymorphs were studied using first-principle calculations based on density functional theory. We found a new promising MoS2 candidate for photocatalytic and photovoltaic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…The resulting elastic coefficient E zzzz was noted as 51.2 and 49.3 GPa, respectively. For four-layered SMoS, E zzzz and E yyzz are highly coinciding with the experimental bulk sample [48] as well as DFT reported values [49,50] for multi-layered systems. The e zzz coefficient is 0.07 nC m −1 for SeMoS-a to SeMoS-e (see Figure 2c).…”
Section: Resultssupporting
confidence: 86%
“…The resulting elastic coefficient E zzzz was noted as 51.2 and 49.3 GPa, respectively. For four-layered SMoS, E zzzz and E yyzz are highly coinciding with the experimental bulk sample [48] as well as DFT reported values [49,50] for multi-layered systems. The e zzz coefficient is 0.07 nC m −1 for SeMoS-a to SeMoS-e (see Figure 2c).…”
Section: Resultssupporting
confidence: 86%
“…97 The polymorphic molybdenum disulfide (MoS 2 ) typically has the trigonal prismatic phase (semiconducting 2H-phase), octahedral phase (metallic 1T-phase), and distorted 1T-phase (semi-metallic 1T′-phase). [98][99][100] Guo et al demonstrated phase-/defect-engineered MoS 2 @TiO 2 catalysts for plasmonic solar water splitting. 101 The phase transition from 2H-to 1T-MoS 2 induced by the hydrothermal treatment coupled with the surface vacancies (V S ) was responsible for the enhanced localized surface plasmon resonance, leading to a superior H 2 yield rate of 308 μmol h −1 cm −2 , which was superior to the state-of-the-art plasmonic catalysts.…”
Section: Advantages Of Facet and Phase Engineering For Water Splittingmentioning
confidence: 99%
“…On the other hand, low-index faceted nanocrystals showed high stability as well as enhanced catalytic activity with their low surface energy. In 1996, Markovic et al compared the Pt low-index single crystal of ( 111), (100), and (110), and the order of HER activity increased in the sequence of ( 111) < (100) < (110). 190 At the same time, research has been conducted to enhance the stability of noble metal catalysts by making full use of lowindex facets.…”
Section: Pec Water Splittingmentioning
confidence: 99%
“…A single layer of MoS 2 has a sandwich structure of S-Mo-S, where the Mo atoms are covalently bonded with the S atoms ( Figure 1 ). MoS 2 has several polymorphs, including 1T 1 , 1T 2 , 1H, 2T, 2H, 2R 1 , 2R 2 , 3H a , 3H b , 3R, and 4T [ 25 , 26 , 27 , 28 , 29 ]. Among them the 1T MoS 2 , 2H MoS 2 , and 3R-MoS 2 polymorphs of MoS 2 have been most investigated for different applications [ 25 , 27 , 28 , 29 ].…”
Section: Atomic-scale Structure Of Mosmentioning
confidence: 99%
“…MoS 2 has several polymorphs, including 1T 1 , 1T 2 , 1H, 2T, 2H, 2R 1 , 2R 2 , 3H a , 3H b , 3R, and 4T [ 25 , 26 , 27 , 28 , 29 ]. Among them the 1T MoS 2 , 2H MoS 2 , and 3R-MoS 2 polymorphs of MoS 2 have been most investigated for different applications [ 25 , 27 , 28 , 29 ]. A single-layer 1T MoS 2 sheet is metallic and has good electrical properties [ 30 , 31 ], while single-layer 2H MoS 2 and 3R-MoS 2 sheets behave as a semiconductor with a direct band gap [ 28 , 32 ].…”
Section: Atomic-scale Structure Of Mosmentioning
confidence: 99%